Implications of perceived tenure security and property rights protection in Burkina Faso - Ibrahim Musah; Michael Ayerter Nanor; Kwasi Kwafo Adarkwa (Cogent Social Sciences)
The study examines perceived tenure security in Burkina Faso, focusing on socio-cultural factors, authority relations, state politics, and gender dynamics. It identifies challenges in tenure security despite legal reforms, emphasising the subjective nature of tenure security and its dependence on individual perceptions. The findings highlight significant disparities in perceived tenure security based on socio-cultural and gender factors, emphasising the need for policies that address these specific challenges and promote equitable access to land and property rights. This study contributes to understanding the complexities of tenure security in Burkina Faso and offers insights for policy formulation and implementation across similar geographical settings.